Cancer in thyroglossal duct cysts. Issue 3 (18th November 2021) - Wong, Jessica; Lee, James C.; Grodski, Simon; Yeung, Meei; Serpell, Jonathan
Abstract: Background: Thyroglossal duct cysts (TDC) account for 7% of midline neck swellings. TDC carcinoma (TDCC) is rare, reported in 1% of all TDCs. We aimed to describe the incidence of TDCC, the accuracy of fine needle aspiration cytology (FNAC), and to identify suspicious, predictive ultrasound (USG) features. Method: A cross sectional study of TDC patients in the Monash University Endocrine Surgery Database from 2001 to 2021. Results: Eighty‐six patients had surgery for TDC, of median age 48 and a female preponderance (62%). Preoperative USG was used in 85% and FNAC in 57%. There were six cases (7%) of TDCC with papillary thyroid cancer (PTC). USG in five TDCC cases showed a solid nodule within the cyst wall. FNAC was undertaken in five TDCC cases from the solid nodule; malignant in one and suspicious for malignancy in two. Two TDCC patients had concurrent total thyroidectomy (TT), and three subsequently had a TT. Multifocal thyroid PTC was found in two patients. One patient had a recurrence in the lateral lymph nodes, nine years after excision of the TDCC and TT. All patients are alive and well with no distant metastases (median follow up 11 years). Conclusion: The 7% incidence of TDCC is higher than the usually reported 1% in the literature. We recommend a preoperative USG to evaluate the TDC, thyroid gland and cervical lymph nodes, and an FNAC to target the solid component of the TDC, and favour total thyroidectomy for all patients with TDCC. Abstract : Incidence of thyroglossal duct cyst carcinoma is higher than what is reported in the literature. We recommend a preoperative ultrasound and fine needle aspiration cytology to target the solid component of thyroglossal duct cysts. We recommend Sistrunk operation for all thyroglossal duct cysts.